Effect of lanthanide ion doping on Mg−Al mixed oxides as active acid−base catalysts for fatty acid ethyl ester synthesis - de Souza Rossi, Jessika [UNESP]; Perrone, Olavo Micali [UNESP]; Siqueira, Marcos Rechi [UNESP]; Volanti, Diogo Paschoalini [UNESP]; Gomes, Eleni [UNESP]; Da-Silva, Roberto [UNESP]; Boscolo, Mauricio [UNESP] (Elsevier, 2019)
MgAl-hydrotalcites (HT) containing 1–2% of the lanthanide ions La3+, Ce3+ and Lu3+ were evaluated as heterogeneous catalysts in the transesterification process for fatty acid ethyl ester (FAEE) synthesis in order to understand the effect of the high ionic-radii of these metals in the material structure and their catalytic activity. The addition of lanthanides to the catalysts resulted in a decrease of the thermal degradation temperature as well as the specific surface, but, on the other hand, it increases the basicity, crystallinity, and improve the yield in biodiesel production. In general, MMOs with 1% of lanthanides showed higher yields than those with 2%, and the oxide with 1% of Lu3+ reached the best catalytic result for ethanol biodiesel production (84%), about 4.5 times greater than the reference material.
Keywords: Fatty acid ethyl ester; Hydrotalcite; Layered double hydroxide; Rare-earth; Transesterification